Total Synthesis of Geranyl-Resorcinols Isolated from Mushrooms of Genus Hericium - Kobayashi, Shoji (Synthesis, 2022)
This Short Review covers the total synthesis of tetraketide-based meroterpenoids, i.e. geranyl-resorcinols, isolated from the mushrooms of genus Hericium. Some of these compounds are believed to be involved in the unique health-promoting effects of Hericium erinaceus. Herein, more than seventy natural products identified so far have been classified into seven-types based on both assumed biosynthetic pathways and chemical structures, and the successful total syntheses are summarized according to the structural type.1 Introduction2 Pioneering Synthetic Study3 Total Synthesis of Geranyl-Resorcinol with a Geranyl Side Chain (Types 1, 3, and 6)4 Total Synthesis of Geranyl-Resorcinol with an Oxidized Geranyl-Derived Side Chain (Types 2, 4, and 7)5 Conclusion
Keywords: mushroom; Hericium erinaceus; meroterpenoid; geranyl-resorcinol; total synthesis; biosynthetic pathway